Determinants of Tax Avoidance on Basic Materials Companies - Yohana Deswita Situmorang; Umiaty Hamzani; Nina Febriana Dosinta (Institut Bisnis dan Informatika Kesatuan, 2025)
This study analyze the effect of profitability, leverage, and company size on tax avoidance in basic materials sector cmpanies listed on the Indonesia Stock Excange (IDX) during the 2021-2023 period. The study is motivated by Indonesia’s low tax ratio, which reflects a high potential for corporate tax avoidance practices. This research contributes empirical evidence from the basic materials sector, which has received limited attention in prior studie regarding financial factors influencing tax avoidance behavior. Data were collected from 34 companies with 94 observations selected through a purposive sampling technique. The study employs an associative quantitative approach using multiple linear regression analysis to examine the relationship between independent variables and tax avoidance. Ttax avoidance is measured using the Effective Tax Rate (ETR), profitability with Return on Assets (ROA), leverage with Debt to Assets Ratio (DAR), and company size with the natural logarithm of total assests. The results show that profitability has a significant effect on tax avoidance, while leverage and company size have no significant effect. Simultaneously, the three independent variables influence tax avoidance, but explain only 7% of the variation observed. Keywords: Tax Avoidance, Profitability, Leverage, Company Size